Rhodium(iii)-catalyzed oxidative annulation of isoquinolones with allyl alcohols: synthesis of isoindolo[2, 1-b]isoquinolin-5(7H)-ones. Issue 2 (15th December 2021) - Jiang, Jinyuan; Liu, Jidan; Yang, Zhenke; Zheng, Jieying; Tian, Xin; Zheng, Liyao; Liu, Zhao-Qing
Abstract : An efficient method to construct isoindolo[2, 1- b ]isoquinolin-5(7 H )-ones via a Rh(iii )-catalyzed direct C–H oxidative annulation of isoquinolones with allyl alcohols has been developed. Abstract : An efficient rhodium(iii )-catalyzed direct C–H oxidative annulation of isoquinolones with allyl alcohols as C1 synthons has been successfully developed. This protocol enables the straightforward synthesis of structurally diverse isoindolo[2, 1- b ]isoquinolin-5(7 H )-ones with high atom economy, tolerates a broad spectrum of functionalities, and is applicable to one-pot operation from readily available N -methoxybenzamides.